The difference of lumbar alignment between the standing and handstand positions of divers - Narita, T.; Kaneoka, K.; Takemura, M.; Miyakawa, S.; Ooyama, K. (Sport Science Research, 2011)
The purposes of this study were to evaluate the lumbar alignment of divers in the standing and handstand positions. This study included 14 elite junior males divers in Japan. X-ray images of the lumbar alignment were taken at a medical facility, and evaluated using image analyzer software to determine the lumbar lordosis angle, which was formed by the upper edge of the first lumbar vertebra and the lower edge of the fifth lumbar vertebrae. The chi square test was used to examine the relationship between low back pain and lumbar lordosis. The results of the test showed no significant relationship between lumbago and the lumbar lordosis. The t-test comparing the two groups (decrease and increase lordosis group), revealed a significant difference between the two in the standing position. The greater angle group showed a significantly smaller angle in standing (25.2±3.4°) than those in the smaller angle group (33.1±5.0°).The major findings of this study were 1) male divers with larger lumbar lordosis on standing had decreased lumbar lordosisin the handstand position, and 2) less lumbar lordosis on standing was associated with increased lumbar lordosis in the handstand position.